Identification of Inhibiting and Supporting Factors for Managerial Performance at PT Anugrah as a Pharmaceutical Company - Andriana Nurmalasari; Deti Mulyo Harsono (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to identify the inhibiting and supporting factors affecting managerial Performance at PT Anugrah, a leading pharmaceutical company in Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews with 15 middle-to-senior level managers and analysis of company documents. Thematic analysis revealed that managerial Performance is primarily supported by transformational leadership, regular competency development programs, and a transparent performance-based reward system. Conversely, key inhibiting factors include excessive bureaucratic procedures interdepartmental communication gaps, and inadequate digital infrastructure. The findings align with existing literature on performance management while highlighting industry-specific challenges in the highly regulated pharmaceutical sector. The study provides practical recommendations for PT Anugrah including leadership development initiatives, streamlining operational processes, and enhancing digital transformation efforts. These findings contribute to the broader discourse on human resource management in regulated industries, offering insights for similar pharmaceutical companies seeking to optimize managerial effectiveness. Limitations include the single-company focus and potential respondent bias, suggesting the need for future quantitative studies across multiple pharmaceutical firms to validate these findings.